Обоснование метода учета сжимаемости потока при течении в диафрагмах с острыми кромками - Тарасов, Александр Иванович; Литвиненко, Оксана Алексеевна; Михайлова, Ирина Александровна (НТУ "ХПИ", 2018)
В статье на основе CFD анализа обоснован метод учета сжимаемости воздуха при течении через диафрагму с острыми кромками. Показано, что расчет массового расхода при заданных давлениях перед и за диафрагмой может быть выполнен с достаточной точностью, если использовать известные зависимости для коэффициента гидравлических потерь давления для несжимаемой среды при условии введения поправки на сжимаемость. Показано, что в отличии от коэффициента гидравлического сопротивления, который зависит только от геометрических размеров диафрагмы при Re > 10⁵, коэффициент расхода зависит от отношения давлений перед и за диафрагмой. Поэтому использование коэффициента гидравлического сопротивления является более предпочтительным. Определение числа Маха при сверхкритическом отношении давлений представляет определенную сложность, так как область, где M > 1 имеет место в суживающейся струе на некотором расстоянии от диафрагмы. Несмотря на это, в инженерных расчетах предложено, в качестве определяющего размера использовать диаметр отверстия, и все параметры потока приводить к живому сечению диафрагмы. При этом вводиться поправка на коэффициент гидравлического сопротивления по методу, изложенному в статье.

Based on CFD analysis this scientific paper substantiates the method of taking into account the compressibility of air passing through the orifice with sharp edges. It was shown that the mass flow rate can be calculated with a sufficient accuracy for specified pressures before and after the orifice if known relationships of hydraulic pressure loss coefficients are used for the incompressible medium provided the compressibility correction is made in the form of a factor (1 + M²/4).Such an approach allows us to use experimental relationships for the definition of the coefficient of hydraulic resistance for pressure ratios before and after the orifice P₁*/P₂ in a wide pressure range. The CFD analysis data showed that the flow rate coefficient depends on the pressure ratio P₁*/P₂ in contrast to the hydraulic resistance coefficient that depends only on geometric orifice dimensions at Re > 10⁵. Therefore the use of hydraulic pressure ratio is more preferable. The definition of Mach number at a supercritical pressure ratio faces certain difficulties, because the domain where M > 1 is situated in the converging jet at a certain distance from the orifice. In spite of this fact the engineering computations suggest to use the aperture diameter as a key size and all the flow parameters must be reduced to the orifice flow section. The hydraulic resistance coefficient correction is made using the method described in the scientific paper. For supercritical pressure ratios the compressibility (1 + M²/4), correction of the coefficient of hydraulic resistance is not sufficient. Using the correction for this domain of pressure ratios as described in previous scientific papers of the authors results in the correct tracking of flow choking.
Substantiating the tracking method of the air flow compressibility in the orifices with sharp edges
Keywords: система охлаждения; газовая турбина; гидравлическое сопротивление; расход воздуха; cooling system; gas turbine; hydraulic resistance